(3QhM GdQhM ajeG MOK HYO GdeGFI GdJGSYI ef GdaJf hGdaJhMs - (3YjSi Hi dWa Gddg Hf GdeWgQ Hf TQa GdOjf Gdjefis
(3BNQgG (B:s
(3BNQ eG ajgG Edi SfI (B972 s
(3fSNI KGfjIs
(3hefg bWYI UhQJ ef ecJHI GdHdOjI HGdCScfOQjI (B3643(3Ls
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B144 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdHdOjI HGdCScfOQjI (B(3643(3L(B) s
Keywords: (3GdJGQjNs